The application of Islamic personal law in Myanmar : legal issues and prospects - Than, Mar Lar (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2017)
This dissertation generally focuses on identifying, highlighting and examining the application of Islamic personal law in Myanmar together with the legal issues and prospects for its effective administration. This research thus specifically aims to study the existing legal framework; examine the legal issues and problems affecting the effective administration and application of Islamic personal law in Myanmar; compare with selected Muslim minority countries of Southeast Asia, and suggest appropriate legal models for the the effective administration and application of Islamic personal law in the country. The study is by its design a qualitative one. The researcher therefore adopts a socio-legal research approach by using both doctrinal and empirical methods. For the doctrinal, the researcher analyses, relevant laws, judicial decisions and literature while for method the empirical method, the research is based data from face-to-face unstructured interviews. The research sample was determined through purposive convenience sampling method. The researcher also uses comparative legal research method by comparing the administration and application of Islamic personal law in Myanmar with those of other Muslim minority countries principally Thailand, Philippines and Singapore. This comparison was to be useful to provide samples of legal measures for application to solve the problems and legal issues of the application of Islamic personal law in Myanmar. This research reveals that although Myanmar Muslims have been allowed during the British colonial era to practice their religion and to apply Islamic law to their personal affairs, the government has not shown any political will to help Muslims to effectively apply it. The study shows that the government has not put in place a legal framework for the application and administration of Islamic personal law in Myanmar. The study also finds that the government has officially given jurisdiction over Islamic personal law matters to civil courts, which are manned by judges who are neither qualified nor have knowledge of Islamic law. This has led to several problems including occasioning miscarriage of justice, adulterating Islamic law on certain matters, etc. The study also reveals that consequent to the problems identified, Islamic person law in Myanmar is not as developed as in other Muslim minority countries in Southeast Asia. The study thus proposes models for application of Islamic personal law in Myanmar.